2017
DOI: 10.1371/journal.pone.0183863
|View full text |Cite
|
Sign up to set email alerts
|

Temporal variability in shell mound formation at Albatross Bay, northern Australia

Abstract: We report the results of 212 radiocarbon determinations from the archaeological excavation of 70 shell mound deposits in the Wathayn region of Albatross Bay, Australia. This is an intensive study of a closely co-located group of mounds within a geographically restricted area in a wider region where many more shell mounds have been reported. Valves from the bivalve Tegillarca granosa (Linnaeus, 1758) were dated. The dates obtained are used to calculate rates of accumulation for the shell mound deposits. These d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 45 publications
1
22
0
Order By: Relevance
“…A local ΔR value of -103±16 radiocarbon years (Ulm 2010) is used here in preference to other values (e.g. Petchey et al 2013;Rhodes et al 1980) and as per other recent work in the region (Holdaway et al 2017;Morrison 2014). All calibrated radiocarbon ages are presented at the 2σ (95% confidence) level and individual ages are given as calibrated age-ranges.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…A local ΔR value of -103±16 radiocarbon years (Ulm 2010) is used here in preference to other values (e.g. Petchey et al 2013;Rhodes et al 1980) and as per other recent work in the region (Holdaway et al 2017;Morrison 2014). All calibrated radiocarbon ages are presented at the 2σ (95% confidence) level and individual ages are given as calibrated age-ranges.…”
Section: Methodsmentioning
confidence: 99%
“…In an intensive study of four shell matrix sites located at the Wathayn outstation, they determined a high degree of variability existed between shell matrix sites, including hiatus periods in the formation of some mound sites. An expanded program of research focused on shell mound features followed, and sought to understand the temporal and spatial variability of a large number of sites at one locality, encompassing both shell matrix deposits (Fanning et al 2018;Holdaway et al 2017) and earth mounds (Brockwell et al 2017). This required a major program of field sampling to obtain stratigraphic profiles, column samples and radiocarbon determinations from 70 shell matrix features within a study area with at least 158 identified sites and some 212 radiocarbon determinations (Holdaway et al 2017).…”
Section: Previous Researchmentioning
confidence: 99%
See 3 more Smart Citations